A topology optimization approach to structure design with self-supporting constraints in additive manufacturing. Issue 2 (25th February 2022) - Wu, Zijun; Xiao, Renbin
Abstract: The manufacturability model of complex structure is the premise of manufacturing, and it is necessary to consider material properties, structure design, manufacturing constraints, and so on. However, due to the inconsistent restrictions between design and manufacturing, it is not easy to obtain the manufacturable structure that matches its design performance using layer-wise manufacturing. This paper presents a topology optimization method for manufacturable form, which incorporates the self-supporting factors such as overhang angle and length based on the characteristics of the generic additive manufacturing process. The support relationship between the supporting and supported elements in self-supporting constraints is mapped to a cascade relationship between two adjacent layers. To avoid a low-density structure supporting multiple high-density ingredients, we establish a fabrication model using the smax and smin operators. Also, the sensitivity analysis and variable updating method are given under the Solid Isotropic Material with Penalization method. Furthermore, numerical examples are shown to validate the correctness and superiority of this proposed self-supporting structure design method. Graphical Abstract: